Separate amenities : topographics of recreational spaces in South Africa - Bezuidenhout, Vincent (Michaelis School of Fine Art, 2014)
The body of photographs discussed in this document examine the way in which the landscape was constructed to enforce separation, in the form of separate amenities, during the time of apartheid in South Africa. This project is situated within the context of a long history of representation of the landscape, but I will position my practise within the more recent political history of apartheid during which separate amenities were created. Referring to David Goldblatt's interpretation of structures with regards to his representation of the South African landscape I will examine both the political and structural history of these locations.